Electronic Structure of (Organic‐)Inorganic Metal Halide Perovskites: The Dilemma of Choosing the Right Functional. Issue 1 (17th December 2021) - Vona, Cecilia; Nabok, Dmitrii; Draxl, Claudia
Abstract: Organic–inorganic metal halide perovskites (HaPs) are intensively studied for their light‐harvesting properties. Owing to the interplay between strong electron–electron interaction and spin‐orbit coupling (SOC), their quantitative theoretical description is still a challenge as evidenced by the wide variety of results available in literature. Here, various methodologies for computing their electronic structure are evaluated, also accounting for SOC. More specific, the G W $GW$ approach as well as variants of the hybrid functionals PBE0 and HSE are at the center of the investigations. For both functionals, methods to determine the mixing parameter α are explored, and for HSE, the impact of the screening‐parameter ω is investigated. An extensive investigation of PbI2, a precursor of many HaPs, leads to the conclusion that hybrid functionals with α tuned by the density‐based mixing method are most suitable for obtaining band gaps comparable to G 0 W 0 $G_0W_0$ results. Moreover, this methodology is transferable to CsPbI3, and the same behavior is expected for the entire family of lead–iodine perovskites. Abstract : Computing the electronic structure of organic–inorganic halide perovskites accurately, remains challenging. The spread of values that different available methodologies obtain for the energy gap, is enormous. This study shows, that properly parametrized hybrid functionals are suitable for this task, and that the procedure adopted for PbI2, the precursor of lead‐iodide perovskites, is transferable to the whole family of these materials.